Let's evaluate the algebraic expressions step by step for \( x = \frac{1}{3} \).
-
Expression: \( 18 - 30x \)
Substituting \( x = \frac{1}{3} \): \[ 18 - 30 \left(\frac{1}{3}\right) = 18 - 30 \cdot \frac{1}{3} = 18 - 10 = 8 \]
Filling in the blank: \[ 18 - 30\left(\frac{1}{3}\right) = 18 - 10 \quad \Rightarrow \quad 10 \]
-
Expression: \( 2(9 - 15x) \)
Substituting \( x = \frac{1}{3} \): \[ 2\left(9 - 15\left(\frac{1}{3}\right)\right) = 2\left(9 - 15 \cdot \frac{1}{3}\right) = 2\left(9 - 5\right) = 2 \cdot 4 = 8 \]
Filling in the blank: \[ 2(9 - 15x) = 2(9 - 15\left(\frac{1}{3}\right)) = 2(9 - 5) \quad \Rightarrow \quad 4 \]
Thus, the filled blanks are:
- \( 10 \)
- \( 4 \)
Both calculations lead to the final value of \( 8 \) when simplified.